Influence of diclofenac on activated sludge bacterial communities in fed-batch reactors - Kraigher, Barbara (Array, 2021)
Research background. The occurrence and environmental toxicity of pharmaceuticals have recently attracted increasing attention. Diclofenac is a highly consumed non-steroidal anti-inflammatory drug, which is often detected in wastewaters, but investigations of its influence on bacteria are scarce. Experimental approach. We investigated the influence of this pharmaceutical on bacterial community in activated sludge exposed to increasing concentrations of diclofenac in fed-batch reactors over 41 days. Nitrification activity of the activated sludge was measured and changes in bacterial community structure were followed using culture-independent molecular method (terminal restriction fragment length polymorphism, T-RFLP) and by the cultivation approach. Results and conclusions. Nitrification activity was not detectably influenced by the addition of diclofenac, while the main change of the bacterial community structure was detected only at the end of incubation (after 41 days) when diclofenac was added to artificial wastewater as the only carbon source. Changes in community composition due to enrichment were observed using cultivation approach. However, taxonomic affiliation of isolates did not match taxons identified by T-RFLP community profiling. Isolates obtained from activated sludge used as inoculum belonged to five genera: Comamonas, Arthrobacter, Acinetobacter, Citrobacter and Aeromonas, known for their potential to degrade aromatic compounds. However, only Pseudomonas species were isolated after the last enrichment step on minimal agar plates with diclofenac added as the sole carbon source. Novelty and scientific contribution. Our results suggest that the selected recalcitrant and commonly detected pharmaceutical does not strongly influence the sensitive and important nitrification process of wastewater treatment.